2000
DOI: 10.1080/07350015.2000.10524853
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Regional Cost of Living

Abstract: The American Chamber of Commerce Research Association (ACCRA) produces the only source of publicly available regional cost of living data which, this paper suggests, may provide misleading information. An evaluation of the quality of the ACCRA indexesconcludes that they contain substantial errors and biases, predominantly from the estimated prices, although error also is introduced by the choice of index formula. To evaluate the ACCRA index, this paper uses category indexes produced by BLS researchers, Kokoski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…The only regional cost-of- Unfortunately, the sample is voluntary, and the number of MSAs covered each quarter varies. Moreover, numerous studies have found the ACCRA index to be unreliable (Dumond et al, 1999,) and subject to significant bias from various sources, including sampling error, sampling bias, and aggregation bias (Koo, 2000). It also does not include a number of key metropolitan areas (Fosu, 1999).…”
Section: Data Source and Methodologymentioning
confidence: 99%
“…The only regional cost-of- Unfortunately, the sample is voluntary, and the number of MSAs covered each quarter varies. Moreover, numerous studies have found the ACCRA index to be unreliable (Dumond et al, 1999,) and subject to significant bias from various sources, including sampling error, sampling bias, and aggregation bias (Koo, 2000). It also does not include a number of key metropolitan areas (Fosu, 1999).…”
Section: Data Source and Methodologymentioning
confidence: 99%
“…12. A further weakness of ACCRA data, identified by Koo et al (2000), is that, because participation in the survey varies each quarter, the base (100) value in each period is just the average of the cities included, not a fixed concept. Therefore, ACCRA data cannot be used for time-series measures of COL. 13.…”
Section: Resultsmentioning
confidence: 99%
“…Koo et al (2000) identify several potential biases in market basket measures such as ACCRA. First, because baseline indices count all cities equally rather than by population weighting them, the overall baseline (i.e.…”
Section: Summary and Evaluation Of Approachesmentioning
confidence: 99%
“…In contrast, the SCOL reflects how much more expenditure an individual needs in region b, to maintain his same level of utility as in region a given the migration of the consumer from a to b. By keeping the utility constant, an estimation of the SCOL facilitates the comparison of the differences in the cost of living across cities (Koo et al, 2000). In summary, the SCOL provides a different perspective than the RPI, for interregional comparisons.…”
Section: Introductionmentioning
confidence: 98%